2015
DOI: 10.3389/fpsyg.2015.01534
|View full text |Cite
|
Sign up to set email alerts
|

Association between facial expression and PTSD symptoms among young children exposed to the Great East Japan Earthquake: a pilot study

Abstract: “Emotional numbing” is a symptom of post-traumatic stress disorder (PTSD) characterized by a loss of interest in usually enjoyable activities, feeling detached from others, and an inability to express a full range of emotions. Emotional numbing is usually assessed through self-report, and is particularly difficult to ascertain among young children. We conducted a pilot study to explore the use of facial expression ratings in response to a comedy video clip to assess emotional reactivity among preschool childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Several engineers have assumed that the relationships between emotional states and facial expressions were established by the theory proposed by Ekman (1971) and have developed automated coding tools or artificial intelligence to read people’s emotions from their facial expressions based on that theory (e.g., Terzis et al, 2010). Several researchers used such tools to infer emotional states in a number of different situations, including while viewing films in individuals with and without mental disorders (Fujiwara et al, 2015) and while consuming food (Kostyra et al, 2016). However, our data suggest that the inner emotional states estimated from facial expressions based on the current theory may differ from the participants’ actual emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…Several engineers have assumed that the relationships between emotional states and facial expressions were established by the theory proposed by Ekman (1971) and have developed automated coding tools or artificial intelligence to read people’s emotions from their facial expressions based on that theory (e.g., Terzis et al, 2010). Several researchers used such tools to infer emotional states in a number of different situations, including while viewing films in individuals with and without mental disorders (Fujiwara et al, 2015) and while consuming food (Kostyra et al, 2016). However, our data suggest that the inner emotional states estimated from facial expressions based on the current theory may differ from the participants’ actual emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used FaceReader to examine facial expressions in young children (e.g. Bugos, DeMarie, Torres, & Fuller, 2022 ; Dys & Malti, 2016 ; Fujiwara, Mizuki, Miki, & Chemtob, 2015 ; Morales‐Sánchez, Pérez‐López, Reigal, & Hernández‐Mendo, 2020 ). These studies found that FaceReader intensity ratings of happy and sad facial expressions were significantly associated with preschoolers' self‐reported feelings of happiness and sadness, respectively (Bugos et al., 2022 ; Fujiwara et al., 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bugos, DeMarie, Torres, & Fuller, 2022 ; Dys & Malti, 2016 ; Fujiwara, Mizuki, Miki, & Chemtob, 2015 ; Morales‐Sánchez, Pérez‐López, Reigal, & Hernández‐Mendo, 2020 ). These studies found that FaceReader intensity ratings of happy and sad facial expressions were significantly associated with preschoolers' self‐reported feelings of happiness and sadness, respectively (Bugos et al., 2022 ; Fujiwara et al., 2015 ). Following Fanti, Kyranides, and Panayiotou ( 2017 ), FaceReader intensity values for each emotion were averaged across all frames within each film condition.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the limited language skills of preschool children, the effect of exposure to trauma due to the earthquake is difficult to assess and has been understudied (25). We initiated this cohort in Kesennuma, Miyagi, to clarify the effect of exposure to trauma due to the earthquake in preschool children (24,25).…”
Section: Samplementioning
confidence: 99%
“…Because of the limited language skills of preschool children, the effect of exposure to trauma due to the earthquake is difficult to assess and has been understudied (25). We initiated this cohort in Kesennuma, Miyagi, to clarify the effect of exposure to trauma due to the earthquake in preschool children (24,25). In our prior study, using data from this cohort, we reported an association between facial expressions of preschool children, measured by facial expression recognition software, and child PTSD symptoms (25).…”
Section: Samplementioning
confidence: 99%